2007
DOI: 10.1158/1541-7786.mcr-07-0229
|View full text |Cite
|
Sign up to set email alerts
|

Interference of Macrophage Migration Inhibitory Factor Expression in a Mouse Melanoma Inhibits Tumor Establishment by Up-Regulating Thrombospondin-1

Abstract: Macrophage migration inhibitory factor (MIF) is a pleiotropic cytokine with proinflammatory, proangiogenic, and protumorigenic properties. The molecular mechanisms underlying the role of MIF in tumorigenesis and angiogenesis are not well understood. To address these roles, an interfering MIF (iMIF) RNA was stably introduced into the B16-F10 mouse melanoma cell line, reducing MIF mRNA expression 1.6-fold and MIF protein expression 2.8-fold relative to control cells. When iMIF cells were subcutaneously injected … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 35 publications
0
15
1
Order By: Relevance
“…14,15 In lung cancer MIF expression is associated with increased production of angiogenic CXC chemokines both in vitro, 16 and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 In lung cancer MIF expression is associated with increased production of angiogenic CXC chemokines both in vitro, 16 and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that MIF is markedly overexpressed in lung cancer [1][2][3] and nearly all other common solid tumors; eg, breast, 4 -8 ovarian, 9,10 prostate, 6 -8 bladder, 11,12 and colon cancer, 13 as well as melanoma. 14,15 In lung cancer MIF expression is associated with increased production of angiogenic CXC chemokines both in vitro, 16 and in vivo. 2 High expression of MIF in patients with lung cancer is also associated with a worse prognosis for disease-free and overall survival.…”
mentioning
confidence: 99%
“…Finally, several recent reports have described MIF to activate HIF-1α under hypoxic conditions [78]; this serves to activate a pro-angiogenic transcriptional program that is necessary for tumor progression. MIF downregulates the NK cell receptor NKG2D, as mentioned above, thereby impairing NK cell cytoxicity toward tumor cells [67] and it upregulates the anti-angiogenic factor thrombospondin-1 [79]. Nevertheless, the precise molecular mechanisms by which MIF mediates tumorigenesis in particular tumor types remain to be more precisely elucidated.…”
Section: Mif In Cancermentioning
confidence: 99%
“…B16 melanoma cells express very low levels of TSP1 mRNA, and TSP1 protein was reported to be below detectable levels. 37 When the tumors obtained a volume of 200 mm 3 , half of the mice of Figure 6. TSP1 and CD47 modulate irradiated hindlimb responses to vasoactive challenge.…”
Section: Absence Of Endogenous Tsp1 Does Not Limit Tumor Response To mentioning
confidence: 99%